PSEUDOCAPACITANCE PROPERTIES OF ELECTRODEPOSITED HYBRID FILMS OF POLYANILINE AND MANGANESE DIOXIDE ON STAINLESS STEELS - Tung, Ngo Duc; Thu Hang, Le Thi (Vietnam Journal of Chemistry, 2012)
Hybrid films of polyaniline and manganese dioxide (PANi/MnO2) were synthesized on stainless steels in different solutions containing aniline and MnSO4 through potential cycling technique. The obtained films showed pseudocapacitive properties from 0 to 0.65 vs Ag/AgCl in aqueous solution of 0.5 M Na2SO4. While in 0.5 M H2SO4, the films displayed characteristic redox peaks of polyaniline (PANi) on cyclic voltammograms. The codeposition of MnO2 with PANi had dramatic effect on capacitive behavior of the obtained hybrid films. In comparison with the sample pure PANi only achieving the specific capacitance of 420 F/g, after co-deposition with MnO2, capacitive behavior was improved significantly. A specific capacitance maximum of 508F/g was obtained responding to sample M50 prepared in the solution containing 50 mM Mn2+ at a scan rate of 5mV/s. The sample also displayed a coulombic efficiency 98% over 800 cycles with 67% specific capacitance maintained.